NILAI-NILAI GOTONG-ROYONG DALAM TARI MBUAH PAGE (ANALISIS SEMIOTIKA NILAI-NILAI GOTONG-ROYONG DALAM TARI MBUAH PAGE PADA ACARA ADAT MERDANG-MERDEM DI DESA PERBESI KECAMATAN TIGABINANGA KABUPATEN KARO SUMATERA UTARA) - Evariana BR Brahmana; Christina Rochayanti; M. Edy Susilo (Jurnal Ilmu Komunikasi, 2009)
This research, entitled “Nilai-nilai Gotong-royong Dalam Tari Mbuah Page” (Analisis Semiotika Nilai-nilai Gotong-royong Dalam Tari Mbuah Page pada Acara Adat Merdang-merdemdi Desa Perbesi Kecamatan Tigabinanga Kabupaten Karo Sumatera Utara). This research starts from the assumption that the Mbuah Page dance as one of the traditional arts are not just as a means of entertainment, but loaded with deep values. This dance is one of the traditional dance of the Karo people who are still found in traditional event Merdang-Merdem in Perbesi Village . This dance is used as media to convey the message of values mutual assistance. Mbuah Pagedance describes how villagers conducting a series of activities in the fields, ranging from rice planting until harvest results. This research aimed to identify the symbols used in Mbuah Pagedance on Merdang-merdem ceremony. The research method used in this study is qualitative and interpretative methods of inter- pretation Semiotics of Roland Barthes. Analysis of the data in this study are exploratory descrip- tive explanations to describe and explain a phenomenon. Test the validity of data is a source of triangulation to strengthen the analysis in this research. The results mentioned that Mbuah Page dance used the media to convey the message the values of mutual assistance. The message was built by the symbolism inherent in the dance, among others, whole body movements of dancers, musical accompaniment, traditional clothing and other devices all of which have relationships with one another. It can be concluded from this research process have meanings that explain the noble values of mutual help and Mbuah Pagedance became the media to convey the message to the public about the importance of a spirit of mutual assistance in a life together.